ANALISIS PELAYANAN ADMINISTRASI PERNIKAHAN DALAM MENINGKATKAN KEPUASAN MASYARAKAT PADA KANTOR URUSAN AGAMA KECAMATAN ILIR BARAT II KOTA PALEMBANG - silvi Handayni (Jurnal Ilmiah Administrasi Dan Sosial, 2026)
Marriage registration is one of the administrative services available at the Religious Affairs Office orKUA. KUA is an agency that deals directly with the community. Prospective brides and grooms who wish to apply for marriage administration must go to the Religious Affairs (KUA) office. However, in fact, theimplementation of marriage administration applications at the Ilir Barat II District Religious Affairs Officehas problems, as evidenced by the fact that there are still many people who do not know the requirements for marriage administration applications, and there is no timeliness in completing the documents, such as there is  no  certainty  regarding  when  the  documents  will  be  completed.  -  documents  submitted,  as  well  as inadequate  facilities  and  infrastructure  such  as  large  parking  areas,  comfort  in  waiting  rooms  and supporting systems to support service tasks at the Office of Religious Affairs.The type of research used in this research is quantitative research which is intended to provide a clear picture of the problems being studied, interpret and explain the data systematically. The basis of this research  is  a  survey,  namely  the  distribution  of  questionnaires  to  respondents  containing  questions regarding matters related to research. The research results of the Analysis of Marriage Administration Services in Increasing Community Satisfaction at the Office of Religious Affairs have gone well. It would be good to improve further in order to gain public satisfaction and public trust in the services provided. It is a good idea to add facilities and infrastructure, especially in the service room, it should not be integrated with the employee's work space, it should be made separate so that people feel more comfortable so that community satisfaction will have a positive value in the eyes of the community. Keywords: Community Satisfaction Administrative Services